Electrospinning in-situ synthesized NH2-MOF multifunctional air purification nano-fiber membrane and preparation method thereof
A multifunctional air-purifying nanofiber membrane with NH2-MOF structure was prepared by electrospinning and microwave-assisted in-situ synthesis of NH2-ZIF-8, which solved the problem of removing fine particulate matter and carbon dioxide from the air and achieved efficient filtration and carbon fixation.
Patent Information
- Application Number
- CN202411591198.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2044-11-08
AI Technical Summary
Existing technologies are ineffective at removing fine particulate matter (such as PM0.3 and PM2.5) and carbon dioxide from the air, and traditional materials are insufficient in air filtration and carbon sequestration performance.
High-bulk polylactic acid fiber membranes were prepared by electrospinning, and NH2-ZIF-8 was synthesized in situ with microwave assistance. Combining the advantages of polylactic acid and NH2-ZIF-8, NH2-MOF multifunctional air purification nanofiber membranes were prepared.
It achieves efficient filtration of fine particulate matter and efficient carbon fixation, and has a large specific surface area, low air resistance and excellent CO2 adsorption performance, making it suitable for applications such as air purifiers, ventilation systems and personal protective masks.
Smart Images

Figure CN119303459A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of fully degradable fiber membrane materials for high-efficiency air filtration and carbon fixation, and in particular to an electrospinning in-situ synthesized NH2-MOF-based multifunctional air purification nanofiber membrane and a preparation method thereof. Background Art
[0002] Air particulate matter pollution and carbon dioxide emissions are major environmental issues facing the world today. The two are intertwined and pose a serious threat to human health and ecosystems. 0.3 and PM 2.5 ) are mainly sourced from industrial emissions, transportation and agricultural activities. These particulates not only affect air quality, but are also closely related to a variety of health problems, such as respiratory and cardiovascular diseases, especially for children and the elderly. At the same time, carbon dioxide (CO2), as the main greenhouse gas, is mainly emitted from the burning of fossil fuels and industrial production, leading to global warming and climate change, which in turn trigger extreme weather events, ecological imbalance and health risks. Although the direct health hazards of carbon dioxide are relatively small, the climate change effects it causes may lead to deterioration in air quality and resource shortages, indirectly affecting the living environment of mankind. Therefore, it is of great significance to solve the problems of air particulate pollution and carbon dioxide emissions, and to develop multifunctional nanofiber membranes with high-efficiency, low-resistance particulate removal and high-efficiency carbon fixation.
[0003] Metal-organic framework materials (MOFs) are complex compounds self-assembled through coordination bonds between organic ligands and metal ions. Compared with traditional materials, MOFs exhibit larger specific surface area and higher porosity, and are diverse in structure and function. Therefore, they have broad application potential in filtration, gas adsorption and separation, and catalysis. Among them, aminated zeolite imidazolate framework-8 (NH2-ZIF-8) is a typical MOFs material with strong adsorption capacity, high porosity, large specific surface area and excellent thermal stability. Combining NH2-ZIF-8 with filter materials can significantly improve their filtration performance.
[0004] On the other hand, polylactic acid, as an ideal green material, is derived from starch extracted from plants. It has excellent mechanical properties, biocompatibility and non-toxicity, and is widely used in the field of air filtration. Polylactic acid can be degraded into carbon dioxide and water in nature, and then used by plants through photosynthesis, which reflects its recyclability and sustainable development. In addition, the molecular chain of polylactic acid contains chiral centers, which show shear piezoelectricity and can generate voltage through mechanical action without the need for polarization treatment of an external electric field. This method is simple, efficient and easy to achieve industrial production. Therefore, combining NH2-ZIF-8 with polylactic acid can not only improve the performance of the filter material, but also give full play to the sustainable advantages of polylactic acid. Summary of the invention
[0005] Purpose of the invention: To meet the demand for efficient air purification, the present invention first prepares a polylactic acid fiber membrane with high fluffiness by an electrospinning process; and synthesizes NH2-ZIF-8 on the surface of the polylactic acid fiber by in situ synthesis, thereby obtaining an NH2-MOF-based multifunctional polylactic acid nanofiber membrane; relying on the high fluffiness of the fiber membrane, the synthesis rate of NH2-ZIF-8 on the surface of the polylactic acid fiber can be significantly improved, so that the obtained fiber membrane has the advantages of large specific surface area, strong filtration performance, low air resistance, strong carbon fixation ability, etc., and is a high-performance air purification material with broad application prospects.
[0006] The present invention provides an electrospinning in-situ synthesized NH2-MOF multifunctional air purification nanofiber membrane and a preparation method thereof. The method comprises the following steps:
[0007] Step S1, preparing a polylactic acid solution: dissolving polylactic acid in a solvent to obtain a polylactic acid solution;
[0008] Step S2, preparation of electrospun polylactic acid fibers: the polylactic acid solution obtained in step S1 is subjected to electrospinning combined with electrostatic spraying technology, the humidity around the Taylor cone is controlled by adjusting the electrostatic spray, and the polylactic acid nanofibers are collected on a collector to prepare a polylactic acid nanofiber membrane with high fluffiness;
[0009] Step S3, preparation of MOF synthesis precursor solution: respectively dissolving zinc salt, 2-methylimidazole and aminoimidazole in a solvent, then slowly adding the zinc salt solution to the mixed solution of 2-methylimidazole and aminoimidazole, and stirring and mixing them evenly to obtain a MOF synthesis precursor solution;
[0010] Step S4, preparation of NH2-MOF multifunctional nanofiber membrane: soak the polylactic acid nanofiber membrane obtained in step S2 in the MOF synthesis precursor solution obtained in step S3, synthesize at a constant temperature in a microwave-assisted environment, and simultaneously perform ultrasonic treatment to ensure that the synthesized MOF material has a uniform size. After the synthesis, rinse with deionized water, let stand and dry to obtain the NH2-MOF multifunctional nanofiber membrane.
[0011] In step S1, the solvent is at least one of dimethylformamide, dichloromethane, chloroform, acetone, hexafluoroisopropanol, and ethyl acetate, the mass ratio of the polylactic acid to the solvent is 1:20 to 1:4, and the dissolution temperature is 5 to 60°C.
[0012] In step S2, the output voltage of electrospinning is 8-40 kV, the solution consumption rate is 0.2-3 mL / h, the spinning winding speed is 10-1000 rpm, the receiving distance is 5-28 cm, the spinning temperature is 10-45 ° C, the humidity is 40%-80%, the average diameter of the polylactic acid nanofibers is 100-1000 nm, and the thickness of the fiber membrane is 400-1000 μm.
[0013] In step S2, the electrostatic spraying technology uses an electrospray solution, and the electrospray solution is selected from at least one of deionized water, ethanol, methanol, ethylene glycol, and propylene glycol, and the consumption rate of the electrospray solution is 1 to 5 mL / h.
[0014] In step S3, the zinc salt is at least one of zinc nitrate, zinc acetate, zinc sulfate, zinc chloride, and zinc gluconate, and the aminoimidazole is at least one of 2-aminobenzimidazole, 2-aminoimidazole, 1-3-aminopropylimidazole, and 4-aminoimidazole.
[0015] In step S3, the solvent is at least one of deionized water, anhydrous ethanol, methanol, ethylene glycol, isopropanol, dimethylsulfamide, and dimethylformamide; the mass ratio of 2-methylimidazole to zinc salt is 1:1 to 8:1; the mass ratio of aminoimidazole to zinc salt is 1:1 to 4:1; and the mass ratio of zinc salt to solvent is 1:1000 to 1:100.
[0016] In step S3, the zinc salt solution is slowly added to the mixed solution of 2-methylimidazole and aminoimidazole at a rate of 5 to 100 mL / min, a stirring rate of 50 to 500 rpm, and a stirring time of 10 to 30 min.
[0017] In step S4, the microwave output power used is 100-1000W, the synthesis temperature is 30-100°C, the ultrasonic power is 100-500W, the ultrasonic frequency is 0.5-20KHz, the ultrasonic power is adjustable in the range of 20%-100%, the synthesis time is 2-80min, the stirring speed is 0-600rpm, and the average particle size of the MOF material is 10-990nm.
[0018] In step S4, the drying method used is one of normal pressure drying, reduced pressure drying, freeze drying, vacuum drying, and microwave drying.
[0019] The present invention also provides an electrospinning in-situ synthesized NH2-MOF multifunctional air purification nanofiber membrane, which is prepared by the method described.
[0020] The electrospun in-situ synthesized NH2-MOF multifunctional air purification nanofiber membrane provided by the present invention has significant application advantages in particulate matter filtration and carbon fixation. First, the material can effectively capture fine particles (such as PM) in the air with the support of high specific surface area and nanoporous structure. 0.3 and PM 2.5 ), improve the particle removal efficiency of air purification equipment, and is suitable for application scenarios that require efficient particle filtration, such as air purifiers, ventilation systems, and personal protective masks. In addition, due to the excellent adsorption capacity of NH2-MOF structure for greenhouse gases such as CO2, the nanofiber membrane also shows excellent results in carbon fixation, and can be used to capture and adsorb CO2, reducing industrial emissions and carbon pollution in the environment. This material has a wide range of application potential in air filtration and greenhouse gas emission reduction, and provides innovative technical solutions for improving air quality and controlling carbon emissions in industrial, home, transportation and other environments.
[0021] Beneficial effect: The electrospinning in-situ synthesized NH2-MOF multifunctional air purification nanofiber membrane and its preparation method provided by the present invention prepare polylactic acid nanofibers with high fluffiness, and directly synthesize NH2-ZIF-8 on the surface of each nanofiber in the fluffy fiber membrane by microwave-assisted in-situ synthesis method to obtain a fully loaded NH2-MOF multifunctional air purification nanofiber membrane. The specific surface area of the nanofiber membrane is 300-500m 2 / g, when the air flow rate is 32L / min, the PM 2.5 The filtration efficiency is 99% to 99.9%, and the PM 0.3The filtration efficiency is 98% to 99.9%, the air resistance is less than 40Pa, and the carbon fixation rate can reach 90% to 95%. The preparation method is simple and the conditions are controllable. The prepared multifunctional air purification nanofiber membrane has the remarkable characteristics of large specific surface area, strong filtration performance, low air resistance, and strong carbon fixation ability, which effectively extends the application of biodegradable materials in the fields of air filtration and CO2 capture. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments, and the above and / or other advantages of the present invention will become more clear.
[0023] Figure 1 It is a flow chart of the method of the present invention.
[0024] Figure 2 This is a schematic diagram of the morphology of the NH2-MOF multifunctional nanofiber membrane prepared in Example 1 observed by SEM.
[0025] Figure 3 This is a schematic diagram of the morphology of the NH2-MOF multifunctional nanofiber membrane prepared in Example 2 observed by SEM.
[0026] Figure 4 This is a schematic diagram of the morphology of the NH2-MOF multifunctional nanofiber membrane prepared in Example 3 observed by SEM. DETAILED DESCRIPTION
[0027] Example 1
[0028] like Figure 1 As shown, this embodiment provides a method for preparing an electrospinning in-situ synthesized NH2-MOF multifunctional air purification nanofiber membrane, comprising the following steps:
[0029] S11, preparation of polylactic acid solution: at 30°C, 1 g of polylactic acid was completely dissolved in 10 mL of chloroform to prepare a polylactic acid solution;
[0030] S12, preparation of electrospun polylactic acid fiber: 1.5 mL of the polylactic acid solution prepared in S11 was put into a syringe, and under the conditions of an output voltage of 20 kV, a solution propulsion speed of 1 mL / h, a fiber winding speed of 100 rpm, a spinning temperature of 30°C, and a humidity of 70%, deionized water was sprayed at a propulsion speed of 2 mL / h to form a mist environment around the polylactic acid Taylor cone, and a high-loft polylactic acid nanofiber membrane was obtained by spinning it into a high-loft polylactic acid nanofiber membrane with an average fiber diameter of 400 nm and a membrane thickness of 800 μm;
[0031] S13. Preparation of MOF synthesis precursor solution: first, take 0.5 g of zinc nitrate and dissolve it in 100 mL of water. Then, take 1 g of 2-methylimidazole and 2 g of 2-aminobenzimidazole and dissolve them in 100 mL of water respectively. Then, add the zinc nitrate solution to the mixed solution of 2-methylimidazole and 2-aminobenzimidazole at a rate of 50 mL / min, and stir at 400 rpm for 20 min to obtain a MOF synthesis precursor solution.
[0032] S14, preparation of NH2-MOF multifunctional nanofiber membrane: the electrospun polylactic acid fiber membrane obtained in S12 is immersed in the MOF synthesis precursor solution obtained in S13, and then placed in a microwave-assisted environment for in situ synthesis, wherein the microwave output power is 500 W, the synthesis temperature is 60°C, and ultrasonic treatment is performed at the same time with ultrasonic power of 250 W, ultrasonic frequency of 10 KHz and ultrasonic power regulation of 50%, the synthesis time is set to 30 min, the stirring speed is set to 200 rpm, and after the reaction is completed, it is rinsed with deionized water and allowed to stand and dry to obtain the NH2-MOF multifunctional nanofiber membrane, wherein the average size of the synthesized NH2-MOF material is 100 nm.
[0033] Example 2
[0034] This embodiment provides a method for preparing an electrospinning in-situ synthesized NH2-MOF multifunctional air purification nanofiber membrane, comprising the following steps:
[0035] S21, preparation of polylactic acid solution: at 60° C., 2.5 g of polylactic acid was completely dissolved in 10 mL of acetone to prepare a polylactic acid solution;
[0036] S22, preparation of electrospun polylactic acid fiber: 0.6 mL of the polylactic acid solution prepared in S21 was put into a syringe, and under the conditions of an output voltage of 40 kV, a solution advancing speed of 0.2 mL / h, a fiber winding speed of 1000 rpm, a spinning temperature of 10°C, and a humidity of 80%, ethanol was simultaneously sprayed at a advancing speed of 5 mL / h to form a mist environment around the polylactic acid Taylor cone, and a high-loft polylactic acid nanofiber membrane was obtained by spinning it into a high-loft polylactic acid nanofiber membrane with an average fiber diameter of 800 nm and a membrane thickness of 400 μm;
[0037] S23. Preparation of MOF synthesis precursor solution: first, take 0.2 g of zinc chloride and dissolve it in 100 mL of water. Then, take 1.6 g of 2-methylimidazole and 0.2 g of 2-aminoimidazole and dissolve them in 100 mL of anhydrous ethanol respectively. Then, add the zinc chloride solution to the mixed solution of 2-methylimidazole and 2-aminoimidazole at a rate of 100 mL / min, and stir at 500 rpm for 30 min to obtain a MOF synthesis precursor solution.
[0038] S24, preparation of NH2-MOF multifunctional nanofiber membrane: the electrospun polylactic acid fiber membrane obtained in S22 is immersed in the MOF synthesis precursor solution obtained in S23, and then placed in a microwave-assisted environment for in situ synthesis, wherein the microwave output power is 1000 W, the synthesis temperature is 100°C, and at the same time, ultrasonic treatment is performed under the parameters of ultrasonic power of 500 W, ultrasonic frequency of 20 KHz and ultrasonic power regulation of 90%, the synthesis time is set to 10 min, the stirring speed is set to 0 rpm, and after the reaction is completed, it is rinsed with deionized water and allowed to stand and dry to obtain the NH2-MOF multifunctional nanofiber membrane, wherein the average size of the synthesized NH2-MOF material is 200 nm.
[0039] Example 3
[0040] This embodiment provides a method for preparing an electrospinning in-situ synthesized NH2-MOF multifunctional air purification nanofiber membrane, comprising the following steps:
[0041] S31, preparation of polylactic acid solution: at 5°C, 0.5 g of polylactic acid was completely dissolved in 10 mL of hexafluoroisopropanol to prepare a polylactic acid solution;
[0042] S32, preparation of electrospun polylactic acid fiber: take 3mL of the polylactic acid solution prepared in S31 into a syringe, and set the output voltage to 8kV, the solution propulsion speed to 3mL / h, the fiber winding speed to 10rpm, the spinning temperature to 45°C, and the humidity to 40%. At the same time, a mixed solution of methanol and water (1:1) is sprayed at a propulsion speed of 1mL / h to form a mist environment around the polylactic acid Taylor cone, and a high-loft polylactic acid nanofiber membrane is spun into it, thereby obtaining a high-loft polylactic acid nanofiber membrane with an average fiber diameter of 300nm and a membrane thickness of 600μm;
[0043] S33. Preparation of MOF synthesis precursor solution: first, take 1g of zinc acetate and dissolve it in 50mL of water. Then, take 2g of 2-methylimidazole and 4g of 4-aminoimidazole and dissolve them in 50mL of dimethylformamide respectively. Then, add the zinc acetate solution to the mixed solution of 2-methylimidazole and 4-aminoimidazole at a rate of 5mL / min, and stir at 50rpm for 30min to obtain a MOF synthesis precursor solution.
[0044] S34, preparation of NH2-MOF multifunctional nanofiber membrane: the electrospun polylactic acid fiber membrane obtained in S32 is immersed in the MOF synthesis precursor solution obtained in S33, and then placed in a microwave-assisted environment for in situ synthesis, wherein the microwave output power is 100 W, the synthesis temperature is 30°C, and at the same time, ultrasonic treatment is performed under the parameters of ultrasonic power of 100 W, ultrasonic frequency of 0.5 KHz and ultrasonic power regulation of 20%, the synthesis time is set to 80 min, the stirring speed is set to 300 rpm, and after the reaction is completed, it is rinsed with deionized water and allowed to stand and dry to obtain the NH2-MOF multifunctional nanofiber membrane, wherein the average size of the synthesized NH2-MOF material is 300 nm.
[0045] Example 4
[0046] This embodiment provides a method for preparing an electrospinning in-situ synthesized NH2-MOF multifunctional air purification nanofiber membrane, comprising the following steps:
[0047] S41, preparation of polylactic acid solution: at 20° C., 1.5 g of polylactic acid was completely dissolved in 10 mL of a mixed solution of dichloromethane and dimethylformamide (mass ratio of 1:1) to prepare a polylactic acid solution;
[0048] S42, preparation of electrospun polylactic acid fiber: take 1 mL of the polylactic acid solution prepared in S41 into a syringe, set the output voltage to 20 kV, the solution propulsion speed to 0.8 mL / h, the fiber winding speed to 200 rpm, the spinning temperature to 35°C, and the humidity to 60%, and at the same time, spray water at a propulsion speed of 2 mL / h to form a mist environment around the polylactic acid Taylor cone, and spin it into a high-loft polylactic acid nanofiber membrane to obtain a high-loft polylactic acid nanofiber membrane with an average fiber diameter of 500 nm and a membrane thickness of 500 μm;
[0049] S43. Preparation of MOF synthesis precursor solution: first, take 0.8 g of zinc gluconate and dissolve it in 120 mL of water. Then, take 0.8 g of 2-methylimidazole and 2.4 g of 1-3-aminopropylimidazole and dissolve them in 120 mL of isopropanol respectively. Then, add the zinc gluconate solution to the mixed solution of 2-methylimidazole and 1-3-aminopropylimidazole at a rate of 50 mL / min, and stir at 200 rpm for 20 min to obtain a MOF synthesis precursor solution.
[0050] S34, preparation of NH2-MOF multifunctional nanofiber membrane: the electrospun polylactic acid fiber membrane obtained in S42 is immersed in the MOF synthesis precursor solution obtained in S43, and then placed in a microwave-assisted environment for in situ synthesis, wherein the microwave output power is 800 W, the synthesis temperature is 70°C, and ultrasonic treatment is performed at an ultrasonic power of 400 W, an ultrasonic frequency of 15 KHz and an ultrasonic power regulation of 70%, the synthesis time is set to 15 min, the stirring speed is set to 200 rpm, and after the reaction is completed, deionized water is used for rinsing, and the NH2-MOF multifunctional nanofiber membrane is obtained after standing and drying, wherein the average size of the synthesized NH2-MOF material is 300 nm.
[0051] Comparative Example 1 (no foggy space formed around the Taylor cone)
[0052] The NH2-MOF multifunctional nanofiber membrane was basically prepared by the method of Example 1. The difference is that no electrospray solution was added to create a spray space during electrospinning in this example. Specifically, S11, preparation of polylactic acid solution: at 30°C, 1g of polylactic acid was completely dissolved in 10mL of chloroform to obtain a polylactic acid solution; S12, preparation of electrospun polylactic acid fiber: 1.5mL of the polylactic acid solution obtained in S11 was placed in a syringe, and the output voltage was set to 20kV, the solution propulsion speed was 1mL / h, the fiber winding speed was 100rpm, the spinning temperature was 30°C, and the humidity was 70%. Under the conditions, a high-fluff polylactic acid nanofiber membrane with an average fiber diameter of 400nm and a membrane thickness of 800μm was obtained; S13, preparation of MOF synthesis precursor solution: first, 0.5g of zinc nitrate was dissolved in 100mL of water, and then 1g of 2-methylimidazole and 2g of 2-methylimidazole were taken respectively. 2-aminobenzimidazole was dissolved in 100 mL of water, and then zinc nitrate solution was added to the mixed solution of 2-methylimidazole and 2-aminobenzimidazole at an addition rate of 50 mL / min, and stirred at a speed of 400 rpm for 20 min to obtain a MOF synthesis precursor solution. S14, preparation of NH2-MOF multifunctional nanofiber membrane: the electrospun polylactic acid fiber membrane obtained in S12 was soaked in the MOF synthesis precursor solution obtained in S13, and then placed in a microwave-assisted environment for in-situ synthesis, wherein the microwave output power was 500 W, the synthesis temperature was 60 ° C, and at the same time, ultrasonic treatment was performed under the parameters of 250 W ultrasonic power, 10 KHz ultrasonic frequency and 50% ultrasonic power control, the synthesis time was set to 30 min, the stirring speed was 200 rpm, and after the reaction was completed, deionized water was used for rinsing, and the NH2-MOF multifunctional nanofiber membrane was obtained after standing and drying, wherein the average size of the synthesized NH2-MOF material was 100 nm.
[0053] Comparative Example 2 (Aminoimidazole was not used in the preparation of NH2-MOF synthesis precursor solution)
[0054] The NH2-MOF multifunctional nanofiber membrane was prepared basically by the method of Example 2. The difference was that aminoimidazole was not used in the preparation of the NH2-MOF synthesis precursor solution in this example. Specifically, S21, preparation of polylactic acid solution: at 60°C, take 2.5g of polylactic acid and completely dissolve it in 10mL of acetone to obtain a polylactic acid solution; S22, preparation of electrospun polylactic acid fiber: take 0.6mL of the polylactic acid solution obtained by S21 into a syringe, set the output voltage to 40kV, the solution propulsion speed to 0.2mL / h, the fiber winding speed to 1000rpm, the spinning temperature to 10°C, and the humidity to 80%, and at the same time, spray ethanol at a propulsion speed of 5mL / h to form a mist environment around the polylactic acid Taylor cone, and spin it into a high-fluff polylactic acid nanofiber membrane to obtain a high-fluff polylactic acid nanofiber membrane with an average fiber diameter of 800nm and a membrane thickness of 400μm; S23, preparation of MOF synthesis precursor solution: first take 0.2g of zinc chloride and dissolve it in 100mL of water, and then take 1.8g 2-Methylimidazole was dissolved in 100 mL of anhydrous ethanol, and then zinc chloride solution was added to the 2-methylimidazole solution at a rate of 100 mL / min, and stirred at 500 rpm for 30 min to obtain a MOF synthesis precursor solution. S24, NH2-MOF multifunctional nanofiber membrane preparation: The electrospun polylactic acid fiber membrane obtained in S22 was soaked in the MOF synthesis precursor solution obtained in S23, and then placed in a microwave-assisted environment for in-situ synthesis, wherein the microwave output power was 1000 W, the synthesis temperature was 100 ° C, and at the same time, ultrasonic treatment was performed at an ultrasonic power of 500 W, an ultrasonic frequency of 20 KHz, and ultrasonic power was controlled at 90%, the synthesis time was set to 10 min, the stirring speed was 0 rpm, and after the reaction was completed, deionized water was used for rinsing, and the NH2-MOF multifunctional nanofiber membrane was obtained after standing and drying, wherein the average size of the synthesized NH2-MOF material was 200 nm.
[0055] Comparative Example 3 (In the preparation of NH2-MOF multifunctional nanofiber membrane, microwave + ultrasound assistance is not used to promote in-situ synthesis)
[0056] The method of Example 3 was basically adopted to prepare the NH2-MOF multifunctional nanofiber membrane, except that microwave assistance was not used to promote in-situ synthesis in the preparation of the NH2-MOF multifunctional nanofiber membrane in this example. Specifically, S31, preparation of polylactic acid solution: at 5°C, take 0.5g of polylactic acid and completely dissolve it in 10mL of hexafluoroisopropanol to obtain a polylactic acid solution; S32, preparation of electrospun polylactic acid fiber: take 3mL of the polylactic acid solution obtained in S31 into a syringe, and set the output voltage to 8kV, the solution propulsion speed to 3mL / h, the fiber winding speed to 10rpm, the spinning temperature to 45°C, and the humidity to 40%. At the same time, a mixed solution of methanol and water (1:1) is sprayed at a propulsion speed of 1mL / h to form a mist environment around the polylactic acid Taylor cone, and a high-fluff polylactic acid nanofiber membrane is spun into it to obtain a high-fluff polylactic acid nanofiber membrane with an average fiber diameter of 300nm and a membrane thickness of 600μm; S33, preparation of MOF synthesis precursor solution: first, take 1g of zinc acetate and dissolve it in 50mL of water, and then take 2g of 2-methylimidazole and 4g of 4-aminoimidazole was dissolved in 50 mL of dimethylformamide, and then zinc acetate solution was added to the mixed solution of 2-methylimidazole and 4-aminoimidazole at an addition rate of 5 mL / min, and stirred at a speed of 50 rpm for 30 min to obtain a MOF synthesis precursor solution. S34, NH2-MOF multifunctional nanofiber membrane preparation: The electrospun polylactic acid fiber membrane obtained in S32 was immersed in the MOF synthesis precursor solution obtained in S33, and then placed in a microwave-assisted environment for in-situ synthesis, wherein the microwave output power was 100 W, the synthesis temperature was 30 ° C, and at the same time, ultrasonic treatment was performed under the parameters of 100 W ultrasonic power, 0.5 KHz ultrasonic frequency and 20% ultrasonic power control, the synthesis time was set to 80 min, the stirring speed was 300 rpm, and after the reaction was completed, it was rinsed with deionized water, and after standing and drying, the NH2-MOF multifunctional nanofiber membrane was obtained, wherein the average size of the synthesized NH2-MOF material was 300 nm.
[0057] Structural characterization and performance testing
[0058] Scanning electron microscope (SEM) observation: The microstructure of the NH2-MOF multifunctional nanofiber membrane (e.g. Figure 2 , Figure 3 and Figure 4 shown).
[0059] Specific surface area test: The nitrogen adsorption isotherm was measured at 77 K using a gas adsorption instrument (ASAP 2060, Micromeritics, USA).
[0060] Filtration performance test: LZC-K automatic filter material tester (Suzhou Huada Instrument Equipment Co., Ltd.) was used to test the same area (area 113.04cm 2 )Air filtration performance and pressure drop parameters of the friction self-powered polylactic acid fiber filter membrane. The gas flow rate was set to 32 L / min. Each group of fiber membranes was tested at least in 3 different positions, and the results were taken as the average value.
[0061] CO2 adsorption performance test: Through the self-built gas adsorption performance test platform, medical grade CO2 with a concentration of 99.5% was used, and a standard commercial regulator was used to introduce an appropriate amount of CO2 into the test bench. A portable CO2 sensor was used to monitor the concentration of CO2 in real time, and the adsorption efficiency of the nanofiber membrane for gas was calculated after 1 hour of adsorption.
[0062] Antimicrobial activity test: Staphylococcus aureus and Escherichia coli were cultured in contact with and without contact with NH2-MOF multifunctional nanofiber membrane, respectively. Then the number of bacteria in the culture dish was counted, and the antibacterial efficiency of NH2-MOF multifunctional nanofiber membrane against different bacteria was calculated.
[0063] Experimental results: Figure 2 As shown, the fiber surface of the NH2-MOF multifunctional nanofiber membrane prepared in Example 1 has obvious NH2-ZIF-8 nanoparticles synthesized, and it can be found that NH2-ZIF-8 is synthesized more evenly on the fiber surface, which can significantly increase the contact sites of NH2-ZIF-8 with particles and gases, which is conducive to the efficient capture and adsorption of them. Figure 3 and Figure 4 It can also be found in the SEM image that relatively uniform NH2-ZIF-8 nanoparticles are synthesized on the surface of the fiber.
[0064] In addition, Table 1 shows the performance test results of Examples 1 to 4 and Comparative Examples 1 to 4. It can be seen from the table that the specific surface area of Examples 1 to 4 can reach up to 444.8 m 2 / g, having a very excellent specific surface area, which can provide more adsorption sites for the polylactic acid nanofiber membrane to capture particles and adsorb toxic gases. It is worth noting that in Comparative Example 2, it can be found that the specific surface area of the nanofiber membrane also reaches 344.7m 2 / g, which is significantly better than other comparative examples. This is mainly because although there is no addition of aminoimidazole, the presence of 2-methylimidazole also promotes the synthesis of ZIF-8 on the fiber surface, thus also showing a higher specific surface area.
[0065] Table 1
[0066]
[0067] At the same time, PM was removed at a high air flow rate of 32 L / min. 2.5 and PM 0.3 The performance of PM was measured, as shown in Table 1. 0.3 The filtration efficiency can reach 99.2% to 99.7% for PM 2.5 The filtration efficiency can reach 99.7% to 99.9%. Compared with Comparative Examples 1 to 3, the embodiment shows excellent filtration performance. This is mainly because compared with the densely arranged fiber membrane (Comparative Example 1), the fiber membrane with high fluffiness can significantly improve the interception efficiency of particulate matter inside the fiber membrane. In addition, the fiber membrane with high fluffiness is more conducive to the uniform synthesis of NH2-ZIF-8 inside the fiber membrane and on the fiber, thereby better improving the filtration efficiency. Comparative Example 2 also shows better filtration efficiency. This is mainly because ZIF-8 is also well synthesized on the fluffy fiber, and the large specific surface area is also conducive to its efficient interception of particulate matter. Comparative Example 3 has a good filtration efficiency for PM 0.3 and PM 2.5 The filtration efficiency is only 83.4% and 90.27%, which is mainly due to the lack of microwave-assisted catalysis. It is difficult to synthesize complete NH2-ZIF-8 nanoparticles in situ at a constant temperature for a short time. Therefore, the interception of particulate matter is limited, and it mainly depends on the interception of the fiber membrane itself. Secondly, due to the high fluffiness, the prepared NH2-MOF multifunctional nanofiber membrane also shows extremely low air resistance. The air resistance of Examples 1 to 4 at 32L / min is not higher than 40Pa.
[0068] Table 1 compares the antimicrobial properties of the NH2-MOF-based multifunctional nanofiber membranes. From the data in the table, it can be seen that the antimicrobial efficiency of the embodiments is above 97%, and the antimicrobial property of Comparative Example 2 can also reach 97%. This also shows that the NH2-MOF-based multifunctional nanofiber membrane has the effect of inactivating microorganisms. This is mainly because NH2-ZIF-8 has good antimicrobial properties and can inactivate microorganisms. The reason why Comparative Example 2 has a high bacterial filtration efficiency is mainly attributed to ZIF-8, while the main reason for the low antimicrobial properties of Comparative Examples 1 and 3 is that the dense fiber membrane structure in Comparative Example 1 is not conducive to the synthesis of NH2-ZIF-8 on the fiber surface, and Comparative Example 3 lacks the catalytic assistance of microwaves, and it is difficult to synthesize complete NH2-ZIF-8 nanoparticles in a short time of constant temperature synthesis.
[0069] Table 1 also compares the adsorption efficiency of NH2-MOF multifunctional nanofiber membranes for CO2. It can be found that Examples 1 to 4 show excellent adsorption performance for CO2, and the highest adsorption efficiency can reach 94.5%. This is mainly due to the uniform synthesis of NH2-ZIF-8 nanoparticles on the fiber surface, which provides a higher specific surface area for the fiber membrane, and the fluffy fiber can provide more sites for contact with CO2, thereby providing higher adsorption for CO2, and the amino functional groups on NH2-ZIF-8 are weakly alkaline and can react chemically with weakly acidic gases such as CO2, which is also more conducive to the adsorption and capture of CO2. At the same time, it was found through testing that although Comparative Example 2 has a high particle removal efficiency, it has a low adsorption efficiency for CO2, which is mainly attributed to the limited adsorption of CO2 by the synthesized ZIF-8 in Comparative Example 2.
[0070] This shows that the polylactic acid nanofiber membrane with high fluffiness prepared by the method of the present invention and the in situ synthesis of NH2-ZIF-8 nanoparticles on the fiber surface through microwave assisted in order to obtain an NH2-MOF multifunctional nanofiber membrane with high specific surface area, high filtration efficiency, low air resistance, high antibacterial properties and high CO2 adsorption performance has broad application prospects.
[0071] The present invention provides an electrospinning in-situ synthesized NH2-MOF multifunctional air purification nanofiber membrane and a preparation method thereof. There are many methods and ways to implement the technical solution. The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the protection scope of the present invention. All components not specified in this embodiment can be implemented by existing technologies.
Claims
1. A method for preparing a multifunctional air purification nanofiber membrane synthesized by in-situ electrospinning of NH2-MOF, characterized in that: The following steps are involved: Step S1, preparing a polylactic acid solution: dissolving polylactic acid in a solvent to obtain a polylactic acid solution; Step S2, preparation of electrospun polylactic acid fibers: the polylactic acid solution obtained in step S1 is subjected to electrospinning combined with electrostatic spraying technology, the humidity around the Taylor cone is controlled by adjusting the electrostatic spray, and the polylactic acid nanofibers are collected on a collector to prepare a polylactic acid nanofiber membrane with high fluffiness; Step S3, preparation of MOF synthesis precursor solution: respectively dissolving zinc salt, 2-methylimidazole and aminoimidazole in a solvent, then slowly adding the zinc salt solution to the mixed solution of 2-methylimidazole and aminoimidazole, and stirring and mixing them evenly to obtain a MOF synthesis precursor solution; Step S4, preparation of NH2-MOF multifunctional nanofiber membrane: soak the polylactic acid nanofiber membrane obtained in step S2 in the MOF synthesis precursor solution obtained in step S3, synthesize at a constant temperature in a microwave-assisted environment, and simultaneously perform ultrasonic treatment to ensure that the synthesized MOF material has a uniform size. After the synthesis, rinse with deionized water, let stand and dry to obtain the NH2-MOF multifunctional nanofiber membrane.
2. The method according to claim 1, characterized in that In step S1, the solvent is at least one of dimethylformamide, dichloromethane, chloroform, acetone, hexafluoroisopropanol, and ethyl acetate, the mass ratio of the polylactic acid to the solvent is 1:20 to 1:4, and the dissolution temperature is 5 to 60°C.
3. The method according to claim 2, characterized in that In step S2, the output voltage of electrospinning is 8-40 kV, the solution consumption rate is 0.2-3 mL / h, the spinning winding speed is 10-1000 rpm, the receiving distance is 5-28 cm, the spinning temperature is 10-45 ° C, the humidity is 40%-80%, the average diameter of the polylactic acid nanofibers is 100-1000 nm, and the thickness of the fiber membrane is 400-1000 μm.
4. The method according to claim 3, characterized in that In step S2, the electrostatic spraying technology uses an electrospray solution, and the electrospray solution is selected from at least one of deionized water, ethanol, methanol, ethylene glycol, and propylene glycol, and the consumption rate of the electrospray solution is 1 to 5 mL / h.
5. The method according to claim 4, characterized in that In step S3, the zinc salt is at least one of zinc nitrate, zinc acetate, zinc sulfate, zinc chloride, and zinc gluconate, and the aminoimidazole is at least one of 2-aminobenzimidazole, 2-aminoimidazole, 1-3-aminopropylimidazole, and 4-aminoimidazole.
6. The method according to claim 5, characterized in that In step S3, the solvent is at least one of deionized water, anhydrous ethanol, methanol, ethylene glycol, isopropanol, dimethylsulfamide, and dimethylformamide; the mass ratio of 2-methylimidazole to zinc salt is 1:1 to 8:1; the mass ratio of aminoimidazole to zinc salt is 1:1 to 4:1; and the mass ratio of zinc salt to solvent is 1:1000 to 1:
100.
7. The method according to claim 6, characterized in that In step S3, the zinc salt solution is slowly added to the mixed solution of 2-methylimidazole and aminoimidazole at a rate of 5 to 100 mL / min, a stirring rate of 50 to 500 rpm, and a stirring time of 10 to 30 min.
8. The method according to claim 7, characterized in that In step S4, the microwave output power used is 100-1000W, the synthesis temperature is 30-100°C, the ultrasonic power is 100-500W, the ultrasonic frequency is 0.5-20KHz, the ultrasonic power is adjustable in the range of 20%-100%, the synthesis time is 2-80min, the stirring speed is 0-600rpm, and the average particle size of the MOF material is 10-990nm.
9. The method according to claim 8, characterized in that In step S4, the drying method used is one of normal pressure drying, reduced pressure drying, freeze drying, vacuum drying, and microwave drying.
10. Electrospinning in-situ synthesis of NH2-MOF multifunctional air purification nanofiber membrane, characterized in that: The method is prepared by the method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Air filtering membrane based on nano-hybrid modified polylactic acid fiber and preparation method of air filtering membrane
CN115961428A
In-situ MOF stereocomplex polylactic acid micro / nano fiber self-powered filter membrane and preparation method thereof
CN116726729A
Poly(lactic acid) membrane and method of making the membrane
US20170029981A1
Electrospun nanofibrous polymer membrane for use in air filtration applications
US20230167591A1
Cited By
Air filter material and preparation method thereof
CN121243862A